Simple contracts with adverse selection and moral hazard - Daniel Gottlieb; Humberto Moreira (Theoretical Economics, 2022)
We study a principal-agent model with moral hazard and adverse selection. Risk-neutral agents with limited liability have arbitrary private information about the distribution of outputs and the cost of effort. We show that under a multiplicative separability condition, the optimal mechanism offers a single contract. This condition holds, for example, when output is binary. If the principal's payoff must also satisfy free disposal and the distribution of outputs has the monotone likelihood ratio property, the mechanism offers a single debt contract. Our results generalize if the output distribution is "close" to multiplicatively separable. Our model suggests that offering a single contract may be optimal in environments with adverse selection and moral hazard when agents are risk neutral and have limited liability.
Keywords: D82; D86; 330; contract theory; mechanism design; Principal-agent problem